Enhancing Students’ Oral Proficiency: Leveraging Film Watching for Speaking Skill Development - Sapitri, Dian; Hastini, Hastini; Darmawan Darmawan (Journal of General Education and Humanities, 2024)
The purpose of this study is to determine whether or not watching films helps students improve their speaking abilities. Using a pre-experimental research approach, the researcher included just one class in the study. The students of SMA Negeri 5 Palu in the tenth grade made up the research population. The researcher chose the sample through the use of purposive sampling. The 31 students in X M 8 served as the research sample for this study. Instrument testing was employed in the data collection process (pre-test and post-test). The Watching Film method was used to treat the experimental class. The results of the data analysis showed that there was a significant difference between the pre-test and post-test. The researchers discovered that the t-counted (5.16) was higher than the t-table (2.000). It indicates that the theory was approved. In conclusion, watching films helps SMA Negeri 5 Palu tenth-grade students improve their speaking skills.